Protease-Activated Receptor-Stimulated Interleukin-6 Expression in Endometriosis-Like Lesions in an Experimental Mouse Model of Endometriosis - Akihiro Shinohara; Masahiko Kutsukake; Mirai Takahashi; Satoru Kyo; Eiichi Tachikawa; Kazuhiro Tamura (Elsevier, 2012)
The present study was undertaken to investigate the function of protease-activated receptor (PAR) in endometriotic lesions using a mouse model of endometriosis. Unilateral ovariectomy (uOVX) was performed on female nude mice followed by intraperitoneal transplantation of a suspension mixture of immortalized human endometrial epithelial cells (EM-1) and stromal cells (EtsT-499). Endometriosis-like lesions were observed mostly around the dissection site after transplantation. The expression of interleukin (IL)-6 and cyclooxygenase-2 in the lesions was enhanced in uOVX mice compared to non-uOVX animals. In non-uOVX mice, IL-6 mRNA levels were higher in lesions formed with cells that were pretreated with PAR1/2 agonists (thrombin, 10 U/ml and PAR2-activating peptide, 30 μM) compared to untreated, intact cells. Peritoneal IL-6 concentrations were also increased in the PAR1/2 agonists-treated group. IL-6 expression induced by PAR activation was blocked by the treatment of cells with serine protease inhibitors. In cultured endometrial cells, simultaneous treatment with PAR1 and PAR2 agonists significantly increased the expression of IL-6. These results suggest that peritoneal bleeding may accelerate IL-6 expression in endometriotic lesions in part through the activation of PAR. Keywords:: endometriosis, endometrial cell, interleukin (IL)-6, protease-activated receptor (PAR), thrombin